The Role of Adolescents in Preventing Stunting and Early Marriage at Tomohon City - Mareyke Yolanda Lusia Sepang; Henny Pongantung; Kansia Anastasia Terok; Vina Putri Patandung (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Adolescents are the next generation who are currently in an important transitional stage toward adulthood. At this phase, they are highly vulnerable to various influences, including a lack of knowledge about reproductive health, the risk of stunting, and the impacts of early marriage. In response to these conditions, a community service activity was conducted at the Auditorium of STIKes Gunung Maria Tomohon, Tomohon City, with the aim of providing health education to students so that they can better understand the importance of adolescents’ role in preventing stunting and the negative impacts of early marriage. The program was carried out in three stages: planning in collaboration with the BKKBN team and the school, delivering interactive health education using engaging media, and evaluation through a question-and-answer session. A total of 164 students enthusiastically participated in the activity, and the discussion results revealed that reproductive health and early marriage were their primary concerns. It is expected that through continuous education, adolescents will be able to make wiser decisions for their future and contribute to stunting prevention within their communities. Programs like this are essential to be held regularly and to reach more schools.